Principles of Corporate Finance / International Edition: Fourth Edition - Brealey Richard A; Myers Stewart C (Mcgraw Hill, Inc, 1991)
Preface, Value, Why Finance Matters, How to Calculate Present Values, Present Value of Bonds and Stocks, Making Investment Decisions with the Net Present Value Role, Risk, More About the Relationships Between Risk and Return, Capital Budgeting and the Capital Asset Pricing Model, Practical Problems in Capital Budgeting, A Project is Not a Black Box, Where Positive Net Present Values Come From, Financing Decisions and Market Efficiency, An Overview of Corporate Financing, How Corporations Issue Securities, Dividend Policy and Capital Structure, The Dividend Controversy, Interactions of Investment and Financing Decisions, Options, Applications of Option Pricing Theory, Warrants and Convertibles, Debt Financing, Value Risky Debt, Hedging Financial Risk, Leasing, Financial Planning, Sort-Term Financial Decisions, Mergers and International Finance and Pensions, Conclusions, Glossary, Index.
Preface, Value, Why Finance Matters, How to Calculate Present Values, Present Value of Bonds and Stocks, Making Investment Decisions with the Net Present Value Role, Risk, More About the Relationships Between Risk and Return, Capital Budgeting and the Capital Asset Pricing Model, Practical Problems in Capital Budgeting, A Project is Not a Black Box, Where Positive Net Present Values Come From, Financing Decisions and Market Efficiency, An Overview of Corporate Financing, How Corporations Issue Securities, Dividend Policy and Capital Structure, The Dividend Controversy, Interactions of Investment and Financing Decisions, Options, Applications of Option Pricing Theory, Warrants and Convertibles, Debt Financing, Value Risky Debt, Hedging Financial Risk, Leasing, Financial Planning, Sort-Term Financial Decisions, Mergers and International Finance and Pensions, Conclusions, Glossary, Index.